Matrices for radioactive waste immobilization: a review - Pilania, Ritu Kumari; Dube, Charu Lata (Frontiers in Materials, 2023)
Nuclear energy is considered a clean, reliable, and an inexhaustible energy source for power generation. Nuclear power is harnessed from nuclear fission reactions in a dedicated power plant. The by-products (produced in the nuclear power plant) are radioactive and pose a threat to the environment. The safe disposal of nuclear waste is vital to ensure the sustainable use of the nuclear energy. The immobilization of radioactive waste before final disposal is essential for the interim storage and transportation. This review summarises the recent work on glasses, ceramics, and glass-ceramics matrices to immobilize the high-level waste. The synthesis methods, leaching behaviour and radiation resistance of matrices are discussed briefly.